Vietnam’s Inflation During the Period 1995 – 2024 And Some Policy Implications (International Journal of Scientific Research and Management (IJSRM), 2025)
This study focuses on analyzing inflation trends in Vietnam during the 1995-2024 period and assessing the linear relationship between current inflation and past inflation through a linear regression model. The data used in the study is the annual Consumer Price Index (CPI). The research reveals that inflation in Vietnam has fluctuated significantly across different economic periods: stable during 1995-2006, surged during the global financial crisis of 2007-2011, and stabilizing again from 2012-2024. During the 1995-2011 period, regression outcomes demonstrate that current inflation was heavily impacted by previous period inflation with a coefficient of 1,2311, whereas this coefficient decreased to 0,9534 in the 2012-2024 period. This clearly reflects the effectiveness of macroeconomic policies in controlling inflation during 2012-2024. The model achieved high statistical significance with no econometric flaws. The research findings not only elucidate the role of past inflation in influencing current inflation but also provide empirical evidence to support more stable and proactive future monetary and fiscal policy planning.